Application of Surplus Production Model to the Yellowfin Tuna Thunnus albacares in the northern and western parts of Aceh waters. Issue 1 (November 2021) - Rahmah, A; Mardhatillah, I; Damora, A; Muhammad, M; Nurfadillah, N
Abstract: Yellowfin tuna Thunnus albacares is one of pelagic fish that has high potential and economic value in Banda Aceh. Utilization of this resource in Banda Aceh is using purse seine units, with the number of purse seines continuously increasing. Therefore, management needs to be done so that optimal productivity can be maintained. This study discusses the estimation of catch and effort at maximum sustainable yield (MSY) of yellowfin tuna based on catch per unit effort (CPUE) and purse seine production in Banda Aceh during 2013-2018. Mathematical analysis was carried out using the equilibrium approach with the Schaefer model. The highest catch of yellowfin tuna reached 191 tons (July) and the average CPUE for yellowfin tuna was 0.796 tons/trip with CMSY of 2, 482 tons/year and EMSY of 2, 765 trips/year. From 2015 to 2018, the trend of biomass continued to decline and overfishing occurred during this period.